The meaning of religion for patients in cancer treatment - Maier, S. R. O.; Almeida, A. N.; Oliveira, W. S. (Scientific Electronic Archives, 2018)
The objective of the study was to understand the sense of religiosity, assigned by the patients who experience or have experienced cancer treatment. This is a qualitative-descriptive, under the framework of phenomenological analysis in Ales Bello, as a way to understand and analyze the human being in its totality - physical, mental and spiritual. The study was conducted with ten patients at the centre of oncology of a hospital in the north of Mato Grosso. The data were collected through semi-structured interviews. In the present study revealed that patients with cancer show they belong to a diversity of religions. The patients mean the religion as a means of support and sustenance critical in moments of pain and suffering caused by cancer and its treatment. Perceive the religious community as a spiritual support, being able to share feelings, conflicts and your pain. It was possible to infer that the faith can be linked to the treatment of cancer the participants to associate the treatment to some kind of therapy religious.